A growing Noyce Scholarship Program: successes, triumphs and challenges along the way - Sharlonne Rollin Smith (Emerald Publishing, 2024)
Purpose - The article discusses the development and growth of a newly established Noyce Scholarship Program at a Hispanic Serving Institution and the collaborative efforts of the School of Education (SOE) and its partners during the recruitment and retention process. Design/methodology/approach - The author will explore and answer questions: (1) What were the articulated agreements implemented during the recruitment and application process? (2) In what ways did the scholar's professional growth benefit from the dedicated and shared resources of the SOE's partners? (3) How did the process of mentoring transform into a collaborative research effort resulting in presentation experiences? Findings - The balance of triumphs, challenges and success in the program allows room for growth and reflection. Once scholars were admitted and accepted into the program, various supports were implemented to ensure scholars would be given tools needed to become highly effective educators in high-needs schools. In an informal discussion with scholars, they indicated the program taught them the necessary tools and dispositions needed to effectively teach the curriculum in STEM-based classrooms. However, they believed the issues of the program could be solved through constant communication and consideration of scholar input. Scholars also expressed appreciation for experiences encountered for scholar success. Originality/value - The Noyce Scholars Program has provided opportunities for STEM majors to demonstrate hope and vision regarding the teacher shortage, particularly in STEM areas. The story of a professional development school's unpredictable journey in addressing the teacher pipeline will hopefully be a source of valuable information for other Professional Development School (PDS) partnerships. Recruitment, clinical preparation and continuous support of partners will continue to be integral factors in shaping future efforts to address the STEM teacher shortage creating a better world, locally and globally.